Support among healthcare workers for the new mandatory seasonal influenza vaccination policy and its effects on vaccination coverage - Aleksi Hämäläinen; Riitta-Liisa Patovirta; Ella Mauranen; Sari Hämäläinen; Irma Koivula (Annals of Medicine, 2021)
AbstractIntroduction Finland was the first European country to introduce a nation-wide mandatory seasonal influenza vaccination policy for healthcare workers (HCWs) by mandating that administrators of health care institutions only employ vaccinated HCWs. In this study, we examine the effects of the new policy and the view of HCWs on the new policy.Methods A cross-sectional observational study was conducted in Kuopio University Hospital among HCWs working in close patient contact. The statistics on vaccination coverage were obtained from the hospital’s own databases, where employees were asked to self-report their suitability for work. An anonymous survey was sent to HCWs in 2015–2016 (n = 987) and 2018–2019 (n = 821).Results Vaccination coverage increased from 59.5 to 99.6%, according to the hospital’s own records. Among the survey respondents, the seasonal influenza vaccination coverage of HCWs increased from 68.2 to 95.4%. 83.8% of doctors and 49.4% of nurses supported the new policy. 12.7% of doctors and 41.5% of nurses found the new mandate coercive or that it restricted their self-determination.Conclusions Our study confirms the positive effects of mandating the administrators of health care institutions to only employ vaccinated HCWs. The majority (57.9%) of all HCWs supported the new policy, with doctors being more compliant than nurses.Key messagesFinland became the first European country to mandate influenza vaccination for HCWs by mandating that administrators of health care institutions only employ vaccinated HCWs.After the new act, the vaccination coverage of HCWs increased close to 100%.Most of the HCWs supported the new act and did not find it coercive.